2002
DOI: 10.1074/jbc.m109025200
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Pyrimidine Deoxynucleoside Analog Diphosphates

Abstract: Most nucleoside analogs require stepwise phosphorylation to the respective triphosphate metabolites to exert their pharmacological activity. L-and D-dCyd analogs are phosphorylated by cytoplasmic deoxycytidine kinase, and dThd analogs are phosphorylated by cytoplasmic thymidine kinase to the monophosphate metabolites. L-FMAU can be phosphorylated by both cytoplasmic deoxycytidine kinase and cytoplasmic thymidine kinase. dCyd analog monophosphates are further phosphorylated by cytidine/uridine monophosphate kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
35
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(35 citation statements)
references
References 40 publications
0
35
0
Order By: Relevance
“…The last step in the phosphorylation of L-deoxynucleoside analog diphosphates to the respective triphosphates, which are the pharmacologically active metabolites, remained largely unexplored. Through comparison of phosphorylation of several clinically relevant D-deoxynucleoside, D-dideoxynucleoside, and L-deoxynucleoside analog diphosphates by nucleoside-metabolizing enzymes purified from the human hepatic carcinoma cell line HepG2, we recently reported that L-deoxynucleoside analog diphosphates could be phosphorylated by 3-phosphoglycerate kinase (PGK); D-deoxynucleoside analog diphosphates were likely to be phosphorylated by nucleoside diphosphate kinase; and D-dideoxynucleoside analog diphosphates were excellent substrates for creatine kinase (16). Moreover, L-deoxynucleoside analog diphosphates were better substrates for PGK than the corresponding D-deoxynucleoside and D-dideoxynucleoside analog diphosphates (at 200 M).…”
mentioning
confidence: 99%
“…The last step in the phosphorylation of L-deoxynucleoside analog diphosphates to the respective triphosphates, which are the pharmacologically active metabolites, remained largely unexplored. Through comparison of phosphorylation of several clinically relevant D-deoxynucleoside, D-dideoxynucleoside, and L-deoxynucleoside analog diphosphates by nucleoside-metabolizing enzymes purified from the human hepatic carcinoma cell line HepG2, we recently reported that L-deoxynucleoside analog diphosphates could be phosphorylated by 3-phosphoglycerate kinase (PGK); D-deoxynucleoside analog diphosphates were likely to be phosphorylated by nucleoside diphosphate kinase; and D-dideoxynucleoside analog diphosphates were excellent substrates for creatine kinase (16). Moreover, L-deoxynucleoside analog diphosphates were better substrates for PGK than the corresponding D-deoxynucleoside and D-dideoxynucleoside analog diphosphates (at 200 M).…”
mentioning
confidence: 99%
“…Similarly, L-nucleoside diphosphates are phosphorylated to triphosphates by pathways different from those responsible for D-nucleoside diphosphate phosphorylation. 20,21 The limited extent of the background phosphorylation of LT in cells not transduced by HSV-TK-containing vectors 15 does not interfere with the histoautoradiographic imaging of the cells expressing HSV-TK.…”
Section: Discussionmentioning
confidence: 99%
“…This study also emphasizes that contrary to the assumptions that NDPKs phosphorylate all nucleoside analog diphosphates, the structure of the analog is just another variable in determining the substrate specificity of the enzyme. Our earlier studies had in fact suggested that pyrimidine D-dideoxynucleoside analog diphosphates are phosphorylated by creatine kinase (32). Given the diversity of nucleoside analogs currently used or under clinical trials for the treatment of cancer and viral infections, it is important to understand the structure-based distinction in the metabolism of these analogs.…”
Section: Discussionmentioning
confidence: 99%
“…The cells were harvested in cold phosphate-buffered saline containing 20 M dipyridamole (Sigma) and extracted with 15% trichloroacetic acid for 10 min on ice. The supernatant containing the nucleoside and its phosphorylated forms was extracted with a 45/55 ratio of trioctylamine and 1,1,2-trichlorotrifluroethane (32,33). The trichloroacetic acid insoluble pellet representing the nucleotide incorporated into the DNA was washed twice and resolubilized in Me 2 SO prior to evaluation on a Beckman LS5000TD scintillation counter.…”
Section: And [mentioning
confidence: 99%
See 1 more Smart Citation